Disiplin Kerja, Kompensasi, Pendidikan dan Pelatihan Terhadap Kinerja Pegawai - Vemi Fytaloka; Kasinem Kasinem; Hayani Hayani; Mujari Mujari (Journal of Management and Bussines (JOMB), 2023)
This research aims to determine the influence of work discipline, compensation and education and training partially and simultaneously on customer satisfaction at the Lahat Regency Manpower and Transmigration Service. The research method used is quantitative. The research results show, a) the work discipline variable on employee performance, with partial testing obtained a value of 2.104 > 2.01954 and a significant value of 0.042 < 0.05; b) compensation variable on employee performance, with partial testing obtained a value of 2.374 > 2.01954 and a significant value of 0.022 < 0.05; c) the education and training variable with partial testing obtained a significant value of 3.597 > 2.01954, namely 0.001 < 0.05; d) with simultaneous testing, the value obtained was 21, 432 > 2.83 and the significant value was 0.000 < 0.05. In conclusion, work discipline has a positive and significant effect on employee performance at the Lahat Regency Manpower and Transmigration Service. Compensation has a positive and significant effect on employee performance at the Lahat Regency Manpower and Transmigration Service. Education and training have a positive and significant effect on employee performance at the Lahat Regency Manpower and Transmigration Service. Work discipline, compensation, education and training jointly influence employee performance at the Lahat Regency Manpower and Transmigration Service. Keywords: Work Discipline, Compensation, Performance, Education, Training